Budgeting reform in the Covid-19 pandemic era and the response of the local government in Indonesia: A case study in Southeast Sulawesi Province - Kadir, Abdul; Suaib, Eka; Zuada, La Husen (Political Science Program, Universitas Negeri Semarang, 2021)
This article describes budgetary reform policies in the era of the Covid 19 pandemic and the local government's response. This article aims to answer how the regional budgeting mechanism is in the pandemic era and the response of regional apparatus organizations to budgeting reform. The data sources in the article use the literature study method and documents sourced from the Southeast Sulawesi Provincial government and media coverage. This article finds that the Indonesian government issued a policy of budget refocusing in response to the COVID-19 pandemic. This policy applies to all ministries/agencies, including local governments, where local government responses are divided into two groups. Namely, some do budget refocusing, but local governments also do not refocus their budgets. The Southeast Sulawesi Provincial Government took the attitude of refocusing the budget by issuing Governor Regulation Number 10 of 2020; this shows that the regional government is responding to the direction of the central government. However, this policy of budget refocusing does not appear to have the full support of the Regional Warfare Task Force (SKPD) or the bureaucracy, which is subordinate to the governor. This can be seen from several SKPDs that maintain their budgets so as not to experience a significant reduction. This finding shows that although budgeting reform during the pandemic was carried out quickly, each regional apparatus organization's content, minor, and budget scope did not experience much change.